Lessons from a stocktaking evaluation of IFPRI’s experience with country programs - Hazell, Peter B. R.; Place, Frank; Tollens, Eric (International Food Policy Research Institute, 2019)
The International Food Policy Research Institute (IFPRI) has long outposted research staff to engage more closely with individual countries on policy issues in more interactive, demand-driven ways than is possible from IFPRI’s Washington, DC, headquarters. Initially this was done on a relatively small and ad-hoc basis in Bangladesh (1992–94), Pakistan (1985–86), Malawi (1989–94), and Mozambique (1996–99), but in 2003 IFPRI began establishing country-based teams to support the development of broader policies and national strategies related to agriculture, food, and poverty. These teams worked in newly opened country program offices in Africa south of the Sahara (Democratic Republic of the Congo, Ethiopia, Ghana, Malawi, Mozambique, Nigeria, and Uganda) as well as in Bangladesh, China, Costa Rica, India, and Pakistan.